2017
DOI: 10.5194/acp-17-8357-2017
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive atmospheric modeling of reactive cyclic siloxanes and their oxidation products

Abstract: Abstract. Cyclic volatile methyl siloxanes (cVMSs) are important components in personal care products that transport and react in the atmosphere. Octamethylcyclotetrasiloxane (D 4 ), decamethylcyclopentasiloxane (D 5 ), dodecamethylcyclohexasiloxane (D 6 ), and their gas-phase oxidation products have been incorporated into the Community Multiscale Air Quality (CMAQ) model. Gas-phase oxidation products, as the precursor to secondary organic aerosol from this compound class, were included to quantify the maximum… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
75
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(87 citation statements)
references
References 53 publications
12
75
0
Order By: Relevance
“…These species include methylcyclohexane, emitted indoors by glues, paints, and other materials, 127 and cosmetic component cyclopentasiloxane (D5 siloxane). [85][86][87][88][89][90] From TAG PMF results, we observe a similar trend in both Factors 2-D and 2-ND (Figures 4 and 5, respectively) with window opening, which comprises many of the TAG-measured indoor-originating solvents, plasticizers, and personal care product components.…”
Section: Dilution Of Indoor Speciessupporting
confidence: 54%
See 1 more Smart Citation
“…These species include methylcyclohexane, emitted indoors by glues, paints, and other materials, 127 and cosmetic component cyclopentasiloxane (D5 siloxane). [85][86][87][88][89][90] From TAG PMF results, we observe a similar trend in both Factors 2-D and 2-ND (Figures 4 and 5, respectively) with window opening, which comprises many of the TAG-measured indoor-originating solvents, plasticizers, and personal care product components.…”
Section: Dilution Of Indoor Speciessupporting
confidence: 54%
“…73,76,77 Although formaldehyde and acetaldehyde are often observed as by-products of cigarette smoking, 78 supplies, 17,18,21,22,84 and siloxanes are ubiquitous in cosmetics and personal care products. [85][86][87][88][89][90] Benzene, toluene, ethylbenzene, and xylene (BTEX) result from fossil fuel combustion and often originate outdoors. However, known indoor sources include building materials, paints, and cleaning products.…”
Section: Windows Closedmentioning
confidence: 99%
“…A 13.3 L potential aerosol mass (PAM) OFR chamber (Kang et al, 2007(Kang et al, , 2011Lambe et al, 2011a) was used to oxidize vapor-phase D 5 . The OFR was run in the OFR185 mode where O 3 and OH are generated in situ by photolysis of oxygen and water.…”
Section: Aerosol Generation and Characterizationmentioning
confidence: 99%
“…In this work, aerosols are produced using an oxidation flow reactor (OFR), which is a photochemical flow-through reactor. OFRs are small (liter-sized) reactors that use very high oxidation conditions to oxidize reactants (Kang et al, 2007(Kang et al, , 2011Lambe et al, 2011a). Advantages of using OFRs include the ability to quickly test a range of aging conditions, reach high oxidant exposures (multi-day exposure) in minutes, and deploy easily for ambient measurements.…”
Section: Introductionmentioning
confidence: 99%
“…The bathroom was assumed to have dimensions of 43 These reactions were assumed to form silanols. 42,44 Whelan et al 45 suggested that the cVMS (cyclic Volatile Methyl Siloxane) species had a dry deposition velocity of 0.3 cm s −1 outdoors and also that the silanols were more likely to undergo deposition than the parent siloxanes. Based on the method described by Carslaw et al, 35 the outdoor deposition velocity was divided by 20 to provide an indoor equivalent of 0.015 cm s −1 for the cVMS species.…”
Section: Atmospheric Modelmentioning
confidence: 99%